Structural and Optical Properties of Electrodeposited MoS2 Thin Films for Photoelectrochemical (PEC) / Solar Cell Applications - T. Joseph, Sahaya Anand; S., Shariza; Z. M. , Rosli (2011)
Thin films of transition metal chalcogenides (TMC), specifically molybdenum sulphide, MoS2 been prepared by electrodeposition technique on from an aqueous bath of high purity molybdenum and sulphide materials. These materials are useful as high temperature lubricants in the cryogenic rockets and other applications such as in photoelectrochemical (PEC) / solar cells. The films deposited onto stainless steel and indium-tin-oxide (ITO) glass substrates were adherent to the substrate. The obtained films were characterized for their structural and optical properties by XRD, SEM, UV-Vis spectroscopy and Mott-Schottky analysis. X-ray diffraction (XRD) studies confirmed the polycrystalline structure of these films. Scanning electron microscopy (SEM) showed that the films are continuous and uniform. The optical absorption spectrum by UV-Vis spectrophotometer of the films gave an indirect bandgap energy of 1.7 eV. Other semiconducting parameters of the films were obtained by the Mott-Schottky plot.